2014
DOI: 10.1088/0029-5515/54/8/083006
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional distortions of the tokamak plasma boundary: boundary displacements in the presence of resonant magnetic perturbations

Abstract: The three-dimensional plasma boundary displacements induced by applied non-axisymmetric magnetic perturbations have been measured in ASDEX Upgrade, DIII-D, JET, MAST and NSTX. The displacements arising from applied resonant magnetic perturbations (RMPs) are measured up to ±5% of the minor radius in present-day machines. Good agreement can be found between different experimental measurements and a range of models-be it vacuum field line tracing, ideal three-dimensional MHD equilibrium modelling, or nonlinear pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 63 publications
(98 reference statements)
3
49
0
Order By: Relevance
“…Although in many cases ideal MHD models predict the experimental plasma response well, in others a resistive model is needed. 39 Two-fluid modeling shows that the plasma response often screens error fields, 40 but error field penetration can occur when the electron fluid velocity at the rational surface is near zero. 41 Linear, resistive modeling in MARS-F, 42 and linear, non-ideal codes such as M3D-C1 41,43 allow the possibility to include nonideal effects such as rotation, resistivity, and two-fluid physics in modeling of error field screening and penetration.…”
Section: B Plasma Response and 3d Equilibriummentioning
confidence: 99%
“…Although in many cases ideal MHD models predict the experimental plasma response well, in others a resistive model is needed. 39 Two-fluid modeling shows that the plasma response often screens error fields, 40 but error field penetration can occur when the electron fluid velocity at the rational surface is near zero. 41 Linear, resistive modeling in MARS-F, 42 and linear, non-ideal codes such as M3D-C1 41,43 allow the possibility to include nonideal effects such as rotation, resistivity, and two-fluid physics in modeling of error field screening and penetration.…”
Section: B Plasma Response and 3d Equilibriummentioning
confidence: 99%
“…The main conclusion of Ref. [24] is that the measured displacement of the low field side (LFS) midplane boundary depends approximately linearly on the applied resonant field predicted by vacuum field modeling [24]. But it was also observed that in some cases the vacuum modeling clearly underestimates the displacement due to stable ideal kink modes.…”
Section: Introductionmentioning
confidence: 98%
“…The 3D boundary distortion from external MPs has been extensively studied in various machines like ASDEX Upgrade [18,19], DIII-D [20,7,12], MAST [21], JET [22,23] and has been reviewed in Ref. [24]. The main conclusion of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies in combination with MHD modeling indicate that the highest ELM frequency, the strongest density 'pump-out' and the strongest accompanying reduction in the edge pressure gradient are correlated with the coupling of the stable ideal kink modes to resonant components [7][8][9]. The resulting 3D boundary distortion can be many times larger than expected solely from the MP of the vacuum field [10,11]. It has been argued that the MPs modify the peeling-ballooning mode (PBM) stability by a change of edge bootstrap current due to the 'pump-out' [12] or equilibrium currents around rational surfaces [13].…”
mentioning
confidence: 96%
“…To model ξ r , we employ the 3D ideal MHD equilibrium code VMEC [21]. If no strong resistive MHD modes are active, VMEC is able to predict ξ r at the edge [10,17]. For details about its setup for ASDEX Upgrade discharges and the accuracy of VMEC in the presence of rational surfaces, we refer to Ref.…”
mentioning
confidence: 99%